The Use of Foreign Workers in the Era of Ease of Doing Business in Indonesia - Detalim, Mikha (Journal of Private and Commercial Law, 2023)
Investment in developing countries is a crucial aspect. One of the factors considered by investors when making investments is the ease of doing business. With the simplification of regulations on the use of foreign workers in Indonesia, it is hoped that it will provide ease of doing business and attract investors to invest in Indonesia. This article aims to examine the regulations on the use of foreign workers in Indonesia after the issuance of Minister of Manpower Regulation No. 8 of 2021 regarding the Use of Foreign Workers and analyze these provisions as an effort to facilitate business activities in the process of national economic development. This article uses a normative juridical research method with a statutory approach and a conceptual approach. The data used in this article are secondary data collected through documentation and literature study (library research) techniques. The article is divided into three parts. The first part discusses the history and overview of the use of foreign workers in Indonesia. The second part reviews the regulations on the use of foreign workers in Indonesia. In the final part, there is an analysis of the simplification of regulations on the use of foreign workers in Indonesia as an effort to transform society and accelerate national economic development.